76.2k views
2 votes
Solve for the linear system by using substitution
x=6-4y
2x-3y=1

User AndyV
by
5.1k points

1 Answer

7 votes

Hey!

So heres how you would go about doing this:

x = 6-4y

2x - 3y = 1

Plug the value of x which is 6 - 4y into the second equation:

2(6 - 4y) - 3y = 1

12 - 8y - 3y = 1

12 - 11y = 1

-11y = -11

y = 1

Now plug this back into the first equation which gives you x's value:

x = 6 - 4y

x = 6 - 4(1)

x = 6 - 4

x = 2

The answer is:

x = 2

y = 1

User Kenrick
by
5.1k points